God's Word - Michael, Sally, 1953-; Apps, Fred (Phillipsburg, NJ : P&R Publishing, 2015)
"This full-color illustrated primer teaches children what the Bible is, what it says, and why we can trust God's true, powerful Word. In easy-to-understand language, children will learn important theological concepts like the authority, inspiration, infallibility, and inerrancy of Scripture. Each chapter includes discussion questions and family-friendly activities, making this book an excellent devotional for parents of young children."--Publisher description.
The Bible is a message from God -- The Bible was written by God -- The most special book -- The Bible is true -- The Bible is for everyone -- The Bible is understandable -- The Bible is about God -- The Bible's message : I am God ; There is no other God ; Created to show God's greatness ; All have sinned ; The wages of sin ; Saved by grace ; God's gift of eternal life -- God keeps his word -- The Bible is unchanging -- God preserves his word -- The Bible is powerful -- The Bible is the authority -- The Bible gives hope -- The Bible protects from sin -- THe Bible is a guide -- Satan tries to keep us from the Bible -- The Bible was written so that you may believe -- Being a doer and not just a hearer -- The Bible is a treasure.
Includes bibliographical references.
Keywords: Bible -- Juvenile literature; Word of God (Christian theology) -- Juvenile literature; Christian education of children; Michael, Sally, -- 1953-